PENGARUH PROBLEM BASED LEARNING BERBANTUAN VIRTUAL LABORATORY TERHADAP KETRAMPILAN PROSES SAINS DAN PENGUASAAN KONSEP SISWA DI SMA - Hendrik Siswono; Wartono Wartono; Supriyono Koes H (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
This study aims to determine the effect of science process skills and conceptual understandings students through problem based learning (PBL) with real-virtual laboratory, PBL with virtual laboratory, and PBL with real laboratory. This study uses a quasi-experimental and research design with pretest-posttest control group. The study population was a class X SMAN 1 Lumajang the number of 8th grade. The samples were 6 groups of randomly selected class sampling. The first group is the experimental class 1 in 2 class which comprises treatment of PBL with real-virtual laboratory, the second group is experimental class 2 in 2 class which treated PBL with virtual laboratory, and the third group was the control class consisting of 2 classes with PBL treatment real laboratory. Data retrieval science process skills and conceptual understandings of the learning process is done through observation and multiple-choice tests that have expert validation and testing instruments. Virtual laboratory using the PhET‟s software. Analysis of the data using Analysis of Variance (ANOVA) with one lane further Kruskal-Wallis test. The results showed that : (1) Students use PBL with the real-virtual laboratory has the effect of science process skills better. (2) Students use PBL with the real-virtual laboratory give results better conceptual understandings. Keywords: problem based learning, virtual laboratory, science process skills, conceptual understandings.